2015
DOI: 10.1097/mpa.0000000000000331
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Electroporation of the Pancreas Is Feasible and Safe in a Porcine Survival Model

Abstract: This porcine model shows that IRE is feasible and safe in the pancreatic parenchyma. Computed tomography imaging reveals significant changes at 60 minutes after IRE and therefore might serve as an early indicator of therapeutic success. Clinical studies are needed to evaluate the efficacy of IRE in pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 44 publications
1
25
2
Order By: Relevance
“…No severe pancreatitis was reported in these studies. Only mild signs of pancreatitis were observed, characterized by a transient increase in white blood cells, amylase and lipase, which normalized by post-ablation day 3 [38,40]. One animal developed a secondary peak in serum amylase, which normalized again after the wound was opened and packed [38].…”
Section: Pancreasmentioning
confidence: 97%
See 4 more Smart Citations
“…No severe pancreatitis was reported in these studies. Only mild signs of pancreatitis were observed, characterized by a transient increase in white blood cells, amylase and lipase, which normalized by post-ablation day 3 [38,40]. One animal developed a secondary peak in serum amylase, which normalized again after the wound was opened and packed [38].…”
Section: Pancreasmentioning
confidence: 97%
“…No studies reported on outcomes immediately after treatment. However, as early as 1 hour after treatment, gross pathology showed well-demarcated zones of ablation, with some cases reporting oedema, adhesions and haemorrhage [40]. Oedema and adhesions persisted at least up to 7 days post treatment, whereas haemorrhage was no longer seen at this time of evaluation [39,40].…”
Section: Pancreasmentioning
confidence: 99%
See 3 more Smart Citations